2004
DOI: 10.1055/s-2004-814552
|View full text |Cite
|
Sign up to set email alerts
|

Der interessante Fall Nr. 64

Abstract: An 89 year old female patient presented with severe epistaxis and nasal congestion on the right side. On endoscopic examination of the nasal cavity a reddish-bluish tumor has been seen that almost completely filled the posterior part of the cavity. In the MRI a highly vasculated tumor was shown. Performing transnasal endoscopic surgery the tumor was completely removed from the nasal cavity. On histopathologic examination the tumor turned out to be a cavernous haemangioma affecting the posterior end of the righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…10,3336 Discussions of the endoscopically assisted craniofacial resection to remove a sinonasal growth involving the ASB began in the 1990s. 37,38 By 2002, Iwata et al 8 concluded the safety and efficacy of using transnasal endoscopic surgery in epithelioid hemangiomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,3336 Discussions of the endoscopically assisted craniofacial resection to remove a sinonasal growth involving the ASB began in the 1990s. 37,38 By 2002, Iwata et al 8 concluded the safety and efficacy of using transnasal endoscopic surgery in epithelioid hemangiomas.…”
Section: Discussionmentioning
confidence: 99%
“…5–7,10,18,19 However, none have involved or extended to the ASB or were resected without preoperative embolization. Here, we describe the management of a 66-year-old man with a large sinonasal cavernous hemangioma extending to the ASB managed purely endoscopically without preoperative embolization.…”
mentioning
confidence: 99%